RelA is Required for IL-1β Stimulation of Matrix Metalloproteinase-1 Expression In Chondrocytes - Raymond, Lauren (2006)
OBJECTIVE: IL-1β stimulates collagenase-1 (MMP-1) expression in articular chondrocytes, leading to cleavage of type II collagen and irreversible cartilage degradation. The nuclear factor kappa B (NF-κB) pathway is potently activated in IL-1β-stimulated cells and has been implicated as an intermediate in MMP-1 gene expression. However, the roles of individual NF-κB family members during IL-1β-induced MMP-1 gene expression have not been defined. RESULTS: To address the relationship between the NF-κB pathway and MMP-1 gene activation in chondrocytes, primary human articular chondrocyte cultures (HAC) and SW-1353 cells were stimulated with IL-1β over a 24-hour time course and MMP-1, NF-κB1, NF-κB2 and RelA gene expression was assayed. IL-1β-induced MMP-1 expression was comparable in HAC and SW-1353 cells both temporally and quantitatively. MMP-1 gene expression was mirrored by increases in NF-κB gene expresssion, and inhibition of NF-κB nuclear translocation with dominant negative IκBα reduced IL-1β-dependent MMP-1 gene expression. IL-1β activated the NF-κB pathway in chondrocytes, both through phosphorylation and transient degradation of IκBα, as well as through sustained phosphorylation of RelA. Small inhibitory RNAs (siRNA) specific for RelA resulted in significant reduction of MMP-1 mRNA, whereas siRNA for NF-κB1 and NF-κB2 augmented IL-1β-induced MMP-1 expression. CONCLUSIONS: Our data demonstrate that IL-1β activation of the NF-κB pathway is required for IL-1β induction of MMP-1 in chondrocytes and that RelA can work independently of NF-κB1 or NF-κB2 to activate this gene expression program.